Rapid review of the COVID-19 pandemic’s impact on the digitalization of higher education - Chukwuere Joshua (Research on Education and Media)
The digitization of the higher education process in the COVID-19 pandemic (new normal) has created a new technological wave. The COVID-19 pandemic (new normal) presents a great opportunity for higher education institutions (HEIs) to be digital and technologically innovative in their teaching and learning process through digitization. The process of digital transformation of the education system began long ago, but has been accelerated by the new normal created by the COVID-19 pandemic. Digital transformation in higher education institutions (HEIs) has become more intentional, in-demand, and purpose-driven. The COVID-19 pandemic revolutionized the higher education system and other areas of life. This paper examines the aspects of digitization of the higher education process in the new normal created by the COVID-19 pandemic era. This study presents a rapid review of the literature on the research topic. The changes brought about by the COVID-19 pandemic represent what is called the new normal (normality). The study found that the digitization of the higher education process brought accelerated, improved, consolidated, accepted, recognized, and accessible learning. Many digitalization tools such as social media, augmented reality, machine learning, and other emerging technologies are used to accelerate the higher education process during the COVID-19 pandemic (new normal).